Whole genome sequence analysis of the first Australian OXA-48-producing outbreak-associated Klebsiella pneumoniae isolates: the resistome and in vivo evolution. - Björn A Espedido (Public Library of Science (PLoS), 2013)
Whole genome sequencing was used to characterize the resistome of intensive care unit (ICU) outbreak-associated carbapenem-resistant K. pneumoniae isolates. Importantly, and of particular concern, the carbapenem-hydrolyzing β-lactamase gene bla(OXA-48) and the extended-spectrum β-lactamase gene bla(CTX-M-14), were identified on a single broad host-range conjugative plasmid. This represents the first report of bla(OXA-48) in Australia and highlights the importance of resistance gene surveillance, as such plasmids can silently spread amongst enterobacterial populations and have the potential to drastically limit treatment options. Furthermore, the in vivo evolution of these isolates was also examined after 18 months of intra-abdominal carriage in a patient that transited through the ICU during the outbreak period. Reflecting the clonality of K. pneumoniae, only 11 single nucleotide polymorphisms (SNPs) were accumulated during this time-period and many of these were associated with genes involved in tolerance/resistance to antibiotics, metals or organic solvents, and transcriptional regulation. Collectively, these SNPs are likely to be associated with changes in virulence (at least to some extent) that have refined the in vivo colonization capacity of the original outbreak isolate.